The Cochrane Database of Systematic Reviews 1998
DOI: 10.1002/14651858.cd001008
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotherapy for smoking cessation

Abstract: of findings for the main comparison. Hypnotherapy versus behavioural treatments or no treatment for smoking cessation Hypnotherapy versus behavioural treatments or no treatment for smoking cessation Patient or population: people who smoke Intervention: hypnotherapy Comparison: behavioural treatments or no treatment Anticipated absolute effects * (95% CI) Outcomes Risk with control Risk with Hypnotherapy Relative effect (95% CI) № of participants (studies) Certainty of the evidence (GRADE) Comments Study popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 27 publications
2
71
0
8
Order By: Relevance
“…The Cochrane review of nine small trials of hypnotherapy found it no more effective than other behavioural interventions [184]. Hypnotherapy is difficult to evaluate in the absence of a sham procedure to control for nonspecific effects and there is no evidence to support that hypnosis per se has any effect as an aid to smoking cessation.…”
Section: Hypnotherapymentioning
confidence: 99%
“…The Cochrane review of nine small trials of hypnotherapy found it no more effective than other behavioural interventions [184]. Hypnotherapy is difficult to evaluate in the absence of a sham procedure to control for nonspecific effects and there is no evidence to support that hypnosis per se has any effect as an aid to smoking cessation.…”
Section: Hypnotherapymentioning
confidence: 99%
“…75,76 Several alternative therapies have been promoted to reduce withdrawal symptoms, including hypnotherapy, acupuncture, acupressure, laser therapy and electrostimulation, but none have proven to be useful. 77,78 …”
Section: New Nrts and Alternative Therapiesmentioning
confidence: 99%
“…Incentives and competitions do not improve long-term cessation rates (Hey & Perera, 2005). Meta-analysis of trials also reveals no benefit for acupuncture (White et al, 2006) and hypnotherapy (Abbot et al, 1998). However, there is some evidence for the effectiveness of internet support to aid cessation in those already using NRT (Zwartz et al, 2006).…”
Section: Other Interventionsmentioning
confidence: 99%